Answer:
Step-by-step explanation:
question
The function g(x) is created by applying an <em>horizontal</em> translation 4 units left and a reflection over the x-axis. (Correct choices: Third option, fifth option)
<h3>How to determine the characteristics of rigid transformations by comparing two functions</h3>
In this problem we have two functions related to each other because of the existence of <em>rigid</em> transformations. <em>Rigid</em> transformations are transformations applied to <em>geometric</em> loci such that <em>Euclidean</em> distance is conserved at every point of the <em>geometric</em> locus.
Let be f(x) = - 2 · cos (x - 1) + 3, then we use the concept of <em>horizontal</em> translation 4 units in the + x direction:
f'(x) = - 2 · cos (x - 1 + 4) + 3
f'(x) = - 2 · cos (x + 3) + 3 (1)
Now we apply a reflection over the x-axis:
g(x) = - [- 2 · cos (x + 3) + 3]
g(x) = 2 · cos (x + 3) - 3
Therefore, the function g(x) is created by applying an <em>horizontal</em> translation 4 units left and a reflection over the x-axis. (Correct choices: Third option, fifth option)
To learn more on rigid transformations: brainly.com/question/1761538
#SPJ1
Answer:
1
Step-by-step explanation:
Simplifying
3x + 2(4x + -4) = 3
Reorder the terms:
3x + 2(-4 + 4x) = 3
3x + (-4 * 2 + 4x * 2) = 3
3x + (-8 + 8x) = 3
Reorder the terms:
-8 + 3x + 8x = 3
Combine like terms: 3x + 8x = 11x
-8 + 11x = 3
Solving
-8 + 11x = 3
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 8 + 11x = 3 + 8
Combine like terms: -8 + 8 = 0
0 + 11x = 3 + 8
11x = 3 + 8
Combine like terms: 3 + 8 = 11
11x = 11
Divide each side by '11'.
x = 1
Simplifying
x = 1
True because to make a compound event you will need two dependent events
You can write this two ways - as a list of prime factors, or combine like factors and represent their quantity with an exponent.
If you begin by dividing by two, you can do that six times, with a three as the remaining prime factor.
2·2·2·2·2·2·3
OR
2∧6 · 3